The Effectiveness of Zakah, Infaq, Sadaqah (ZIS) Management by BAZDA to Improve the Welfare of Society in Central Java - Heru Sulistyo; Budhi Cahyono (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
The big potential of Zakah, infaq, and Sadaqah (ZIS) in Central Java is one of the instruments for reducing poverty and improving the welfare of the society. This study aims to assess the effectiveness of management ZIS optimally so as to make a significant contribution to poverty reduction and improved well-being. Regulation No. 23 of 2011 on the management of Zakah has provided the legal basis which is very strong in the management of Zakah, by collecting, distributing, and accountability of it.The unit of analysis in this study is the Bazda in Central Java Province. The sample is four districts/cities, including: the city and regency of Semarang, Jepara and Demak district. In addition, the study respondents aremanagers of Bazda, muzzaki, and mustahik in four districts/cities.The findings show that all Bazda have already had database on muzaki and mustahik, but still incomplete, so it cannot be done for the sake of collecting and mapping the distribution of ZIS effectively and efficiently. Moreover, the condition of the building, infrastructure and operational funds sourced budgets have not been able to support the operations and performance of the collection, distribution and reporting effectively and efficiently. Distribution and utilization of ZIS is dominated for the fulfillment of consumer needs and focused on the areas of health, education and social, while, empowering productive business activities is still slightly low, so that it is necessary to have a paradigm shift in the management of the ZIS to make mustahikbecome more productive. It is required a coordinated and integrated cooperation between Bazda District/City, Baz Districts, the regency/state, enterprises, SOEs and private agencies in order to collect ZIS effectively and efficiently and not only dominated merely by the civil servants. Reporting and accountability system, so far, has been conducted in a transparent and accountable through a written report to the District / City Government and Parliament, but some Bazdado not provide it to mustahikin detail, either in book form or through the WEB. Only the district of Jepara which has a complete reporting system, regular, detailed and printed in book form to be sent to the Government, Parliament, and the muzaki of related parties.